Red Shambhala: magic, prophecy, and geopolitics in the heart of Asia - Znamenski, Andrei A. (Publishers Group UK, 2011)
Shambhala, Kalachakra Tantra, and avenging gods of Tibetan Buddhism -- Power for the powerless : the Mongol-Tibetan world and its prophecies -- Alexander Barchenko : budding red Merlin and his ancient science -- Engineer of human souls : Bolshevik cryptographer Gleb Bokii -- Prophecies draped in red : blood and soil in the heart of Asia -- Red prophecy on the march : Mongolia to Tibet -- The great plan : Nicholas and Helena Roerich -- Shambhala warrior in a Western body : Nicholas Roerich's Asian ventures -- Epilogue: The end of red Shambhala